The nexus between board remuneration and performance of state enterprises in Zimbabwe - Mutusva, Sidney (Midlands State University, 2018)
There was an outcry in the past three years over the salaries that State Enterprises and Parastatals bosses were awarding themselves yet service delivery has been lacking. This was termed the “Salarygate” by the media and saw a number of executives being relieved of their duties. The government moved in and set a top salary cap of $6,000 for all heads of SEPs, including benefits. Albeit all the efforts by the government, the Executives continued to receive huge salaries against perennial losses that have been experienced in the country. A positivism philosophy was used with a cross-sectional analysis of 72 SEPs with a total directorship of 504. A sample of 252 respondents were included in the research study. A combination of questionnaires and ordinary least square (OLS) analysis was used to analyse the data. It was found that board remuneration, because they constitute an insignificant part of the total SEPs expenditure have a positive correlationship with firm performance. This is based on the fact that in order to create value for the firm, the board has to be remunerated well. It was also found that there are a number of factors that have a bearing on the firm performance such as industrial/sector performance, economic and legislative environment and the innovation and invention skills within the management of the firms. It was recommended that the Corporate Governance (CG) codes should enshrine the procedures and framework for board remuneration determination and that that board diversity and skills development should be emphasized.